2015
DOI: 10.1074/jbc.m114.627786
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Analysis of CCL28 in the Development of Post-viral Asthma

Abstract: Background: CCL28 is associated with the pathogenesis of acute post-viral asthma. Results: In the absence of viral infection, natively folded CCL28 can induce asthma pathology, whereas unfolded CCL28 cannot. Conclusion:The structure of CCL28 is critical for its role in asthma pathogenesis. Significance: Inhibition of CCL28 presents a novel therapeutic option for the prevention of post-viral asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…Furthermore, we have shown that CCL28 in the absence of a viral infection is sufficient to drive AHR and MCM . Administering an anti‐CCL28 mAb during the viral infection significantly reduced post‐viral MCM and AHR at a late time point (day 49 PI) . These data reiterate the importance of CCL28 to the development of post‐viral lung disease in this animal model.…”
Section: Introductionsupporting
confidence: 67%
“…Furthermore, we have shown that CCL28 in the absence of a viral infection is sufficient to drive AHR and MCM . Administering an anti‐CCL28 mAb during the viral infection significantly reduced post‐viral MCM and AHR at a late time point (day 49 PI) . These data reiterate the importance of CCL28 to the development of post‐viral lung disease in this animal model.…”
Section: Introductionsupporting
confidence: 67%
“…Additionally, tandem mass spectrometry (MS-MS) can in some instances be used to define the pairing of cysteines, like the non-conserved disulfide bond in CCL28 that links C30 to C80 (Thomas et al, 2015), or confirm the locations of posttranslational modifications, like pyroglutamate formation in CCL2 as shown in Figures 4 and 5, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Classic in vitro assays for biological activity can include calcium flux assays or chemotaxis assays (Kar, Srivastava, Andersson, Baratelli et al, 2011; Love et al, 2012; Miller & Krangel, 1992; Neote, DiGregorio, Mak, Horuk et al, 1993; Thomas et al, 2015). Calcium flux assays are those that detect the increase in the cytosol of the secondary messenger calcium that is released as a result of chemokine receptor activation (Love et al, 2012; Miller et al, 1992; Neote et al, 1993).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations